1998
DOI: 10.1099/0022-1317-79-12-2989
|View full text |Cite
|
Sign up to set email alerts
|

A pneumo-virulent United States isolate of porcine reproductive and respiratory syndrome virus induces apoptosis in bystander cells both in vitro and in vivo.

Abstract: Evidence of apoptosis was detected for the UnitedStates porcine reproductive and respiratory syndrome virus (PRRSV) in ATCC CRL11171 cells inoculated with strain ATCC VR2385 and in the tissues of pigs infected with the same strain. Apoptosis was detected by agarose gel electrophoresis, transmission electron microscopy and terminal deoxytransferase dUTP nick end labelling (TUNEL) techniques. By electron microscopy and double-labelling techniques, apoptosis was detected primarily in uninfected bystander cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
78
1
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(88 citation statements)
references
References 29 publications
8
78
1
1
Order By: Relevance
“…Apoptosis occurred both in virus-infected and in non-infected cells. Most apoptotic cells were noninfected, which is in agreement with previous studies [7,24,27].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Apoptosis occurred both in virus-infected and in non-infected cells. Most apoptotic cells were noninfected, which is in agreement with previous studies [7,24,27].…”
Section: Discussionsupporting
confidence: 93%
“…On a morphological basis, the apoptotic cells are assumed to be alveolar and pulmonary intravascular macrophages and mononuclear cells in the alveolar septa. Doublelabelling experiments indicate that most apoptotic cells are non-infected [24,27].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The bystander mechanism suggested in 1997 by Sur et al, was confirmed in 1998 by the same author and others [45,49].…”
Section: Prrsv Is An Apoptotic Inductor Virussupporting
confidence: 61%
“…These results of in vitro apoptosis induction of PRRSV have since been corroborated in vivo by different authors [45,48,49].…”
Section: Prrsv Is An Apoptotic Inductor Virusmentioning
confidence: 52%